Prioritized induced heavy operators applied to political modelling - Avilés Ochoa, Ezequiel; León Castro, Ernesto; Merigó, José M; Perez Arellano, Luis A (2021)
The OWA operator is an aggregation operator developed by Yager (1988) that provides the ability to aggregate different types of information, such as the attitude and expectation of the decision maker. Among the extensions that have been developed and that will be discussed in this paper are the prioritized OWA (POWA) operator (Yager, 2004), which is used in a group decision- making process when not all the decision makers have the same importance in the final results, so to unify the criteria, a prioritized vector is applied. Additionally, the heavy OWA (HOWA) operator (Yager, 2002) is considered; this operator has characteristics that are not bounded to one such as those of the OWA operator; thus, it is possible to  under or overestimate the results according to the expectations. Finally, the induced OWA (IOWA) operator (Yager & Filev, 1999) is applied.